2020
DOI: 10.1101/2020.08.28.273029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ontogeny and Vulnerabilities of Drug-Tolerant Persisters in HER2+ Breast Cancer

Abstract: Despite advances in targeted therapeutics, resistance remains a significant clinical problem in HER2-positive (HER2+) breast cancer and can lead to recurrence, metastasis, and death. “Drug-tolerant persisters” (DTPs), a sub-population of cancer cells that survive via reversible, non-genetic mechanisms, are implicated in resistance to tyrosine kinase inhibitors (TKIs) in several cancer models, but DTPs following HER2 TKIs exposure have not been characterized extensively. We found that treatment of HER2+ breast … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 100 publications
(196 reference statements)
0
22
0
Order By: Relevance
“…As a proven target of miR-335, ALDOA and OCT4 regulate glucose metabolism and homeostasis [25,26,43]. With the increasing incidence of drug-tolerant in various breast cancer subtypes [44][45][46], new therapies or diagnostics could be developed for distant metastasis based on the relationship between circKIF4A and glucose metabolism. Accordingly, our study found that circKIF4A is biologically active in BC and revealed the precise role of the circKIF4A-miR-335- ALDOA/OCT4-HK2/PKM2 axis in the metabolic reprogramming during the development of breast cancer and liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…As a proven target of miR-335, ALDOA and OCT4 regulate glucose metabolism and homeostasis [25,26,43]. With the increasing incidence of drug-tolerant in various breast cancer subtypes [44][45][46], new therapies or diagnostics could be developed for distant metastasis based on the relationship between circKIF4A and glucose metabolism. Accordingly, our study found that circKIF4A is biologically active in BC and revealed the precise role of the circKIF4A-miR-335- ALDOA/OCT4-HK2/PKM2 axis in the metabolic reprogramming during the development of breast cancer and liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous mRNA levels for given genes are often transient, but the expression levels of some genes can be preserved through cell division 7 . The existence of such gene expression memory is of major fundamental and biomedical interest, as it is involved in cancer resistance to drugs [8][9][10][11][12][13][14] , disease onset 11,15 , and differentiation trajectories in development, homeostasis and regeneration [16][17][18][19][20][21] . To study gene expression over cell divisions, scRNA-seq has been combined with different lineage tracing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…While the approach only needs a single time point, performing the assay at several different time points is important for validating the inferred model. We have recently exploited his approach for diverse applications include characterizing drug-tolerant cancer cells [63]- [65], activation of human viruses such as HIV [66], and innate immune response in individual human cells [67].…”
Section: Discussionmentioning
confidence: 99%